PHYSICAL CHARACTERISTICS OF LANDRACE CROSSBRED PORK THAT MARINATED WITH ROBUSTA COFFEE FILTRATE - R., Monicca; Oka, A. A.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2024)
This study aimed to the physical characteristics of crossbreed landrace pork marinated with robusta coffee filtrate. This research was using a completely randomized design consisting of 4 treatments and 5 replications. Marinated pork for 1 hour consisted of P0 (0% robusta coffee filtrate), P1 (10% robusta coffee filtrate), P2 (15% robusta coffee filtrate) and P3 (20% robusta coffee filtrate). The variables observed were pH, cooking loss, weep lose and water holding capacity. Physical characteristics data of landrace pork were analyzed with analysis of variance.The results showed that landrace crossbreed pork marinated with robusta coffee filtrate was not significantly different (P>0.05) at pH: P0 (5.24), P1 (5.35), P2 (5.33), P3 (5.38); weep loss: P0 (6.94%), P1 (7.14%), P2 (7.38), P3 (7.89%); and water holding capacity: P0 (28.07%), P1 (27.85%), P2 (27.09%), P3 (26.85%). However, there was a significant effect on cooking loss (P<0.05) with an average value of P0 (37.36%), P1 (38.82%), P2 (38.72%) and P3 (40.22%). The conclusion of this study is the crossbreed landrace pork marinated with robusta coffee filtrate had no significant effect on pH value, weep lose and water holding capacity, but showed a significant effect on meat cooking loss.